PENGGUNAAN CLICKBAIT HEADLINE PADA SITUS BERITA DAN GAYA HIDUP MUSLIM DREAM.CO.ID - M Rizky Kertanegara (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2018)
The rapid flows of information in the digital age makes online site producers create news that attracted the attention of netizen not only on their main sites but also for social media platforms. The goal is to get a Key Performance Indicator (KPI) which will be useful for the purpose of advertising. The existence of this KPI can be seen from the number of interactions made by readers who clicked, commented, or shared content on their social media accounts. This phenomenon then raises the use of Clickbait Headline, an attractive headline but sometimes trap the curiosity of the readers. To that end, the author wants to see how far the use of Clickbait Headline in Dream.co.id, a news and lifestyle of Muslim sites. In addition, the author also wants to see the use of journalistic ethics code standards on Clickbait Headline. Using content analysis techniques, the author selected samples using purposive sampling from the most viewed article samples in the period 1-21 June 2017. As a result, most articles in Dream.co.id using Clickbait Headline with catafora techniques and have met The Journalistic Ethics Code standards.